(untitled) (VETERINARIA, 2020)
Purulent vaginal discharge (PVD) is one of the postpartum health problems affecting fertility, milk production, and reducing the dairy profitability. The aim of the present study was to investigate the risk factors of PVD in 438 dairy cows. PVD was diagnosed at 21-90 days in milk (DIM) using vaginoscopy. The overall prevalence of PVD was 37% and higher at earlier postpartum (21-30 DIM) (55.3%) compared to intermediate (31-60 DIM) (43.4%) and late (61-90 DIM) (15.3%) postpartum. The main detected risk factors were retained placenta (odds ratio [OR]= 9.3), dystocia (OR=5.33), stillbirth (OR= 5.1), milk fever (OR = 3.4), metritis (OR= 3.3), twin births (OR = 2.8), male calf (OR= 2.5), low BCS around calving (OR=2.8), calving in dry season (OR=1.8), lameness (OR= 1.7) and cow’s breed (OR= 1.6). These statements confirm that PVD is a multifactorial disease, and herd management is a key to reduce the cost of the disease.